2019
DOI: 10.3390/antiox8070207
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Inhibited Ultraviolet Radiation-Induced Hyperpigmentation and Damage in C57BL/6 Mouse Skin

Abstract: Melanin is synthesized through a series of oxidative reactions initiated with tyrosine and catalyzed by melanogenesis-related proteins such as tyrosinase, tyrosinase-related protein-1 (TRP-1), dopachrome tautomerase (TRP-2), and microphthalmia-associated transcription factor (MITF). Our previous study demonstrated that sesamol inhibited melanin synthesis through the inhibition of the melanocortin 1 receptor (MC1R)/MITF/tyrosinase pathway in B16F10 cells. In this study, sesamol was applied to C57BL/6 mouse skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…The results indicated that SFRP5 overexpression lightened the back skin of nude mice, while knockdown of SFRP5 promoted repigmentation of the back skin. Moreover, the most suitable animal model can be generated by using ultraviolet B (UVB) to induce pigmentation in brown guinea pigs 66 , 67 , 68 or C57BL/6J mouse, 69 , 70 and then performing various treatments and observing the color changes. However, because of our limited experimental conditions, UVB induction could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that SFRP5 overexpression lightened the back skin of nude mice, while knockdown of SFRP5 promoted repigmentation of the back skin. Moreover, the most suitable animal model can be generated by using ultraviolet B (UVB) to induce pigmentation in brown guinea pigs 66 , 67 , 68 or C57BL/6J mouse, 69 , 70 and then performing various treatments and observing the color changes. However, because of our limited experimental conditions, UVB induction could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin oil was reported to promote wound healing and have antioxidative, anti-inflammatory, and hypolipemia activities [10,11,12]. Our previous study demonstrated that sesamol inhibited melanin synthesis in B16F10 cells and C57BL/6 mice [13,14]. Sesamin has also been reported to exhibit antioxidative, anti-inflammatory, and antinociceptive activities [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to solar UV directly induces ROS, which may cause oxidative stress, resulting in DNA damage, non-melanoma and melanoma skin cancers, photoaging, and photodermatoses [ 48 , 49 , 50 ]. Melanin is synthesized by a series of reduction–oxidation reactions that are catalyzed by various melanogenic enzymes such as TYR, TRP-2, and TRP-1 [ 8 , 51 ].…”
Section: Discussionmentioning
confidence: 99%